Composition and species diversity of different agroforestry systems in Gondia district of Maharashtra - Kokode, Ashwini V; Taide, Y.B.; Lodh, Uday Kumar; Yadav, Dinesh (Indian Journal of Agroforestry, 2022)
The study was undertaken to assess the composition and species diversity of different agroforestry practices followed by the farmers in the Gondia district of Maharashtra during 2018 – 2019, using the exploratory design of social research. Ten farmers each from 8 villages of Arjuni Morgaon and Deori tehsil were selected for the study. Vegetation analysis was done through quadrate methods with a 0.1 percent sample area. The investigation revealed that the farmers were practicing twelve different agroforestry systems in their field such as Bund plantation, Boundary plantation, Agrisilviculture, Hortisilviculture, Agrisilvipostoral, Agrihortisilviculture, Plantation along irrigation canal, Kitchen garden, Plantation near water source, Block plantation, Scattered plantation and Avenue plantation and this classification of twelve agroforestry systems in gondia district was followed by ( respondents in gondia district) All through this study is based on data generated through survey and prepare data and participatory Rural Appraisal (PRA) efforts have been made to collect to secondary data from the village’s records and meeting with respondents of villages. The vegetation analysis of agroforestry systems for Importannce Value Index (IVI) of 28 trees were recorded grown in different agroforestry system in the study area. The IVI values ranged from 77.54 to 1.73. The lowest value (1.73) was recorded for the Semecarpus anacardiu, while the highest value of IVI (77.54) was recorded for the Tectona grandis, followed by Azadirachta indica (35.65), Butea monosperma (18.63), Leucaena leucocephala (11.67) and Zizyphus mauritiana (10.55). The distribution pattern of species in the study area showed the maximum (2.42) and the minimum (0.048) value. The IVI results show that the tree species with high importance values and variation in ecologically dominant in studied area. Hence, the IVI has helped in understanding the ecological significance of the species in the tropicaldryclimaticzoneofGondiadistrict